PENGARUH LOYALITAS KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN ICHI BENTO DI KOTA BANJAR - Herdis Rusyana; Kusuma Agdhi Rahwana; Barin Barlian (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine and analyze the effect of work loyalty and employee performance on employee performance of Ichi Bento in Banjar City. The method used in this study is causality through a survey approach. With a research sample of 30 employees of the Ichi Bento company, Banjar City. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results showed that Job Loyalty has a very good assessment classification, Employee Performance has a very good rating classification, while Employee Performance has a very good classification for employees of Ichi Bento company Banjar City. Together, work loyalty and employee performance have a significant influence on employee performance at Ichi Bento's employees, Banjar City. Partially, work loyalty has a significant effect on employee performance at the company's employees Ichi Bento Banjar City. Partially, employee performance has a significant effect on employee performance at Ichi Bento company employees, Banjar City